Biodegradable interpenetrating polymer network hydrogel membranes for controlled release of anticancer drug (Asian Journal of Pharmaceutics (AJP), 2015)
Biodegradable interpenetrating polymer network hydrogel membranes of chitosan and gelatin were prepared by solventcasting evaporation method for the controlled release of 5â€fluorouracil (5â€FU), an anticancer drug. The membraneswere characterized by Fourier Transform Infrared Spectroscopy (FTIR), differential scanning calorimeter (DSC), Xâ€rayÂ diffraction (XRD), scanning electron microscopy (SEM) and Tensile strength measurements.The FTIR was used to understand Â the formation of crosslinking and to confirm the absence of chemical interactions between drug and membranes. DSC andÂ XRD studies were performed to understand the crystalline nature of drug after encapsulation into the membranes. SEM wasÂ used to study the surface morphology of the membranes. The in vitro studies were carried out in phosphate buffer pH 7.4 atÂ 37Â°C.The results of controlled release tests showed that the amount of 5â€FU release increased with the increasing the amountÂ of gelatin in the membrane. Moreover, the release rate of drug increased as the amount of drug loaded in the membranesÂ increased. All the results indicated that the prepared membrane was potentially useful in drugâ€delivery systems, and theÂ prolonged release rate was observed up to 12 h.Â Key words: 5â€flurouracil, chitosan, drugâ€delivery systems, gelatin, hydrogel membrane